KETIDAKPUASAN DOSEN ATAS KEPEMIMPINAN KETUA PROGRAM STUDI - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Performance is inseparable from the mental condition of employees. Whether we realize it or not, work requires feelings of pleasure, self-confidence, feelings of enthusiasm and enthusiasm. Therefore, it is important to pay attention to the factors that influence it, one of which is the role of leadership. The leader is the embodiment of the organization, so its existence has a significant effect on the effectiveness and efficiency of organizational activities. This study explicitly aims to express the opinions of the lecturers on their dissatisfaction with the leadership capacity of the head of the study program in carrying out organizational management functions. The proof of the research phenomenon uses a qualitative approach with descriptive methods. The research correspondents are private university lecturers who have the status of institutional developers and have worked for more than 7 years. Data collection techniques used in-depth interviews and discussion groups. The results showed that the greatest dissatisfaction of lecturers was the attitude of the leader's injustice in the distribution of teaching hours, guidance and hearings. There is an imbalance between a group of lecturers and other lecturers, so the issue of the practice of nepotism develops, where the leadership sided only with those closest to him. Next, the lecturer is dissatisfied with the leadership style of responding to a problem, the head of the study program tends to side with the interests of the institution, without considering the interests of the lecturer.